Odpowiedzi

2010-02-23T21:16:16+01:00
A) 2a(b-3)-2b(a-3)=2ab-6a-2ab+6b=4ab-6a+6b
b)a(a+b)+a(a-b)+b(b+a)+(b-a)=a²+ab+a²-ab+b²+ab+b-a=2a²+b²+ab+b-a
c)8x(x+y)-2y(y-x)+1(6x²+8x²)-2y²+5xy=8x²+8xy-2y²+2xy+6x²+8x²-2y²+5xy=22x²+15xy
f)a(a+1)-2(a²- 1a)-a(1-a)=a²+a-2a²+2a-a+a²=2a
g) 0,2(5a+10b)-7(0,1-b)+a-b+=a+2b-0,7+7b+a-b=2a+8b-0,7
32 1 32
2010-02-23T23:32:41+01:00
A)
2a(b-3)-2b(a-3) =
2ab-6a-2ab+6b =
-6a+6b


b)
a(a+b)+a(a-b)+b(b+a)+(b-a) =
a²+ab+a²-ab+b²+ab+b-a =
2a²+ab+b²+b-a


c)
8x(x+y)-2y(y-x)+1(6x² +8x²)-2y²+5xy =
8x²+8xy-2y²+2xy+6x²+8x²-2y²+5xy =
22x²+15xy-4y²


f)
1a (a+1)-2(a² - 1a)-a(1-a) =
a²+a-2a²+2a-a+a² =
2a


g)
0,2(5a+10b)-7(0,1-b)+a-b =
a+2b-0,7+7b+a-b =
2a+8b-0,7

35 4 35